The coverage and extraordinary force of the open mortgage - Risco Sotil, Luis Felipe del (2014)
In Peru, there are legal figures that, despite ofbeing abolished, continue having real effects. Such is the case of the "open mortgage”, which survives in our legal system.In this article, in regard to a recent judicial decision by the Peruvian Supreme Court, the author explains the figures of the “open mortgage” and the “ordinary mortgage”, showing their differences and warning of the inadequacy of equating their jurisprudential treatment.